Interest and Career Planning in Health Economics among the Public Health Students of Purbanchal University, Nepal - Lamichhane, Nabin; Adhikari, Kabita; Pokharel, Shailesh Mani (Shanti Journal, 2024)
Health Economics applies economic principles to the health sector and is a popular area in Public Health. Interest among students in Health Economics is growing. Currently, there are 10 (Universities and health academics) offering Public Health programs (Master or Bachelor of Both). Among them, Purbanchal University (PU) is the second university in Nepal to offer a Bachelor of Public Health (BPH) program since 2001, followed by Tribhuwan University in 1986. Health economics is one of the subjects taught in public health programs. A cross-sectional descriptive study aimed to explore the interest and career planning of Health Economics among public health students at PU School of Health Sciences (PUSHS), a constituent college of PU. A purposive sampling method was adopted, and the study site was selected for the researcher's feasibility.For the quantitative study, a total of 64 students in the final year of BPH and Master of Public health (MPH) were enrolled in the study. Similarly, for a qualitative study, five students who already passed out MPH and completed their health economics course were enrolled. More than two-thirds of students didn't study economics in their school-level curriculum and had inadequate backgrounds foundations in economics, but most of the students showed their interest and career planning in health economics. The majority of the students highlighted the usefulness of health economics for shaping the healthcare system of the country. The study has mixed levels of the status of interest and career planning in Health Economics among public health students of PU. The study suggests further research to be carried out to explore the role and necessity of Health economics in public health programs in a proper and organized way through universities and academic institutions.